Media GAULL: Transformasi Digital untuk Mengasah Kemampuan Berpikir Kreatif di Sekolah Dasar - Deviyanti Pangestu; Oktari Pradina Anggi; Ulfa Nurfitria Ardilla; Kartika Eka Pertiwi (PT. Penerbit Riset Sadwa, 2026)
This community service is driven by the low level of creative thinking skills among fourth-grade students at SDN 1 Sidodadi. The study aims to analyze the influence of GAULL (Wordwall-based educational games) on the creative thinking skills of elementary school students. The community service employed a Quasi-Experimental Design with a Nonequivalent Control Group Design. The population consisted of 58 students, all of whom were included as the sample through a total sampling technique, divided into classes IVA and IVB. Data were collected using test instruments and subsequently analyzed using simple linear regression. The results indicate that the use of GAULL media has a significant effect on students' creative thinking skills. This is evidenced by the statistical analysis, which yielded an Fobserved value of 13.25, exceeding the Ftable value of 4.23 (13.25 > 4.23). Consequently, GAULL media is an effective tool for stimulating creative thinking abilities in elementary school students